Internet of things with artificial intelligence detection and blockchains of crop availability for supply chain management. (5th February 2023) - Anitha, R.; Rai, Dinesh
Supply chain management is a competitive advantage for logistic companies. Before giving a product to a consumer, confirm availability. In this study, we use internet of things (IoT) input-gathering methods to check crop availability. This technology-enabled service inputs weather, moisture, temperature, and soil fertility data and outputs crop availability. Machine learning monitors and predicts crop availability by predicting weed, water, insect, and animal infiltration and crop growth. The paper suggests blockchain-based AI. Energy savings are shown. Decentralized data storage enhances supply chain visibility and quality, boosting farmer participation. Blockchain enhances supply chain security and provenance. Blockchain protects supply chain data transfers. The simulation compares existing approaches and the proposed machine learning-based blockchain. Crop feature extraction and classification are simulated. The proposed ML model is more accurate, exact, and recalled. By 2050, 70% of food will come from agriculture. On a 9-billion-person planet, manufacturers must be more efficient. This newspaper offers IoT and blockchain to tackle these issues.